2SAFE: a health belief model-integrated framework for participatory ergonomics. (4th May 2023) - Zhang, Zhenyu; Lin, Ken-Yu; Lin, Jia-Hua
Abstract: Initiating ergonomics interventions in a business environment requires changes in the behaviour of relevant actors. When participating in an intervention, researchers need to collect and share information with practitioners to help them make better behaviour-related decisions. This paper describes the five-step 2SAFE (Surveillance, Screening, Assessment, Framing, and Evaluation) planning framework, which can be used to guide research-practice collaboration in participatory ergonomics programmes. This framework combines the understanding of work-related musculoskeletal disorders with the principles of the health belief model. This theoretical synthesis empowers the framework to address the following critical challenges: (1) how to make data collection processes attuned to the nature of ergonomic injuries; and (2) how to transform the data collected into immediately usable information for practitioners to change their behaviours. The framework is interdisciplinary and can facilitate transfer of knowledge between ergonomics and health behaviour science. The framework can enhance the ability of researchers to collaborate with practitioners and bring participatory ergonomics programmes closer to success. In the long term, we hope that this framework can lead to more high-quality interventions that are able to prevent work-related musculoskeletal disorders in various industrial settings.